2015
DOI: 10.1055/s-0035-1564730
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Medial Patellofemoral Ligament Reconstruction: A Systematic Review

Abstract: The medial patellofemoral ligament (MPFL) plays a key role in lateral patellofemoral stability, and there has been significant clinical and research interest in MPFL reconstruction (MPFLR) in recent years. The primary objective of this systematic review of clinical studies is to investigate the reported indications for an isolated MPFLR and secondarily to examine some of the reasons reported for not performing an isolated MPFLR. A comprehensive search of the MEDLINE, EMBASE, PUBMED, and Cochrane databases was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
39
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 60 publications
2
39
0
3
Order By: Relevance
“…This aspect is an important consideration when assessing the quality of study results, particularly because previous research found that 88% of MPFL reconstruction studies did not report on the calculation of the study sample size. 24 By defining this relationship in a large real-life cohort, there is always a risk of confounding variables influencing the results. However, because those confounders are as of now undefined and their contribution to outcome is unknown, it is difficult to justify which factors should and should not be accounted for in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect is an important consideration when assessing the quality of study results, particularly because previous research found that 88% of MPFL reconstruction studies did not report on the calculation of the study sample size. 24 By defining this relationship in a large real-life cohort, there is always a risk of confounding variables influencing the results. However, because those confounders are as of now undefined and their contribution to outcome is unknown, it is difficult to justify which factors should and should not be accounted for in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 A systematic review of the indications for MPFL reconstruction noted that trochlear dysplasia was the second most common reason cited in studies for not performing an isolated MPFL reconstruction. 24 In addition, correcting high-grade trochlear dysplasia with a trochleoplasty procedure results in improved outcomes compared with an isolated patellofemoral stabilization. 25 Despite these findings, the indications and thresholds for surgically addressing high-grade trochlear dysplasia in patients with patellofemoral instability remain unclear.…”
mentioning
confidence: 99%
“…Further in vivo studies with the instrumented testing device are warranted to refine the understanding of the role of medial soft tissue stabilisers in patellofemoral biomechanics,9 12 36 to fine-tune diagnostic assessment and to improve the treatment algorithm 37 38…”
Section: Discussionmentioning
confidence: 99%
“…If bony malalignment, trochlear dysplasia, or patella alta is identified during the preoperative workup, an isolated MPFL reconstruction must not be performed. 16 In a systematic review and meta-analysis comprising 14 articles, Schneider et al. 15 reported a 1.2% pooled total risk of recurrent instability after isolated MPFL reconstruction with a reoperation risk of 3.1%.…”
Section: Discussionmentioning
confidence: 99%